An analysis of the Australian illicit tobacco market. Issue 1 (3rd January 2017) - Lauchs, Mark; Keane, Rebecca
Abstract : Purpose: This paper aims to provide an overview of the illicit tobacco market in Australia. It attempts to build a picture of the sources of demand, size of the market and methods of supply. Design/methodology/approach: This paper is based on collation of disparate government reports, industry research, media and court documents. It is a preliminary paper in the absence of better source data. Findings: The market is driven by the extremely high tax on tobacco in Australia. Australia's geography emphasises on large shipments from overseas rather than small-scale smuggling. The likely market is for migrant communities with much higher smoker rates than in the mainstream community. Research limitations/implications: It is not yet possible to conduct a well-focused research because of limited official documentation. Practical implications: Few government agencies focus on tobacco smuggling, and there are no publications providing a strategic picture of the illicit market. This paper fills this gap by collating multiple sources to produce a market profile. Social implications: The Australian Government loses $1bn per year in tobacco tax because of smuggling. The illicit supply also means that the social goal of the tax, namely, dissuading tobacco consumption, is undermined. Originality/value: There are no academic or government publications describing the Australian illicit tobacco market. The only publications are based on research funded by the tobacco industry, which has a vested interest in overstating the size of the illicit market.